CAMELLIA SINENSIS VAR. MADOENSIS (SECT. THEA, THEACEAE), A NEW TAXON FROM VIETNAM - Tran Vu Nguyen; Thi Phuong Nhu Van; Xuan Son Le; Van Ngoc Nguyen; Van Dung Luong; Thi Huy Tra Trinh; Ba Nam Nguyen; Ngoc Trieu Le (Tạp chí Khoa học Đại học Đà Lạt)
Camellia sinensis var. madoensis is described and illustrated as a new variety of Camellia sinensis (section Thea, Theaceae) from Xuan Loc Commune, Song Cau District, Phu Yen Province. The new variety is easily distinguishable from C. sinensis var. sinensis by style free ½ to the base. The ITS sequence of this variety is also different from that of Camellia sinensis and its other varieties, while the matK gene sequences are nearly identical among Camellia taxa.